Predictors of Professional Help-Seeking Intention Toward Depression Among Community-Dwelling Populations: A Structural Equation Modeling Analysis - Li, Xin Yi; Liu, Qian; Chen, Pan; Ruan, Juan; Gong, Xuan; Luo, Dan; Zhou, Yang; Yin, Cong; Wang, Xiao Qin; Liu, Lianzhong; Yang, Bing Xiang (Frontiers in Psychiatry, 2022)
Background: A low intention of professional help-seeking hinders the effective treatment of depression. The factors are from the social, family and individual’s perspectives, however, an understanding of how they interact to predict professional help-seeking intention (PHSI) is not clear. Objectives: To investigate PHSI toward depression in a Chinese community-dwelling population; and construct a predictive model of the PHSI to explore the various factors involved. Methods: Stratified random sampling and Kish table methods were used to identify 2,000 community residents. Participants completed a series of questionnaires to measure general characteristics, PHSI, professional help-seeking attitude, depression stigma, depression knowledge, family function and depression symptoms. Analyses included descriptive statistics and Pearson correlation analysis using SPSS 26.0 and a Structural Equation Model using Amos 22.0. Results: The score of the PHSI was (14.92±9.574). Professional help-seeking attitude (r=0.291, P<0.001) and depression knowledge (r=0.077, P=0.002) were positively related to PHSI, while a negative correlation was found between stigma (r=-0.149, P<0.001) and PHSI. The model of the PHSI indicated a good fit with a CMIN/DF=2.740, RESEA=0.032. The total effect of the factors on the PHSI was listed in the following order:Professional help-seeking attitude (0.676)>Stigma (-0.143)>Depression knowledge (0.088)>Depression symptoms (-0.009)>Family function (0.005). The total effect of depression knowledge on PHSI included a direct negative effect (Beta=-0.266, P<0.001) and an indirect positive effect (0.354) through professional help-seeking attitude and stigma. Also, it was negatively associated with stigma (Beta=-0.153, P<0.001). Depression symptoms were negatively associated with other variables. Family function contributed a positive effect on depression knowledge directly (Beta=0.145, P<0.001) and a totally positive effect (0.033) on stigma. Conclusion: The PHSI toward depression is low among Chinese community residents. Professional help-seeking attitudes, depression knowledge and family functioning were facilitators of PHSI, and stigma and depression symptoms were barriers. This study provides reference for the development of policies to promote community residents to actively seek professional help. Future policies can focus on multi-collaboration among the government, mental health services and families to increase the mental health resources, improve family functioning, enhance mental health literacy of the public and reduce depression stigma to ease the burden of this mental health issue.